Linfoma cardiaco primario: Presentación de un caso. Primary cardiac lymphoma. Presenting a case. - Dr. Jorge Edmundo López Pérez; Dr. Serguei Torres Miranda; Dr. Héctor Conde Cerdeira; Dr. Myder Hernández Navas; Dra. Judith Castro Ballester; Dr. Ronald Aroche Aportela (ECIMED, 2010)
Primary cardiac lymphoma (PCL) is an extremely rare tumor with a difficult and often late diagnosis.The prognosis is poor with a few therapeutically possibilities. We present a primarycardiac non-Hodgkin's lymphoma in a patient of 63 year old, who suffered progressive dyspnea.Some examinations were carried out such as an echocardiography and a nuclear magneticresonance imaging showing a tumor invading the right heart chambers. Due to the infiltrationof the tumor it was not possible to carry out any proceed in the heart surgery. He alsounderwent percutaneous embolization of the tumor. The histological diagnosis was performedafter post-mortem examination. Primary cardiac lymphoma should be included in the differential diagnosis of a right atrial mass, even though is a rare disease. The early diagnosticprocedure and appropriate therapy can result in a long survival time.